Determining the Role of Soluble Urokinase-Type Plasminogen Activator Receptor (suPAR) in Lung Diseases - Can, Ummugulsum; Akdu, Sadinaz (Current Overview on Disease and Health Research Vol. 3, 2022)
SuPAR is a glycoprotein that is released during infections and inflammation. It is a serum-soluble urokinase-type plasminogen activator receptor. Polymorphonuclear neutrophils (PMN) and macrophages secrete urokinase-type plasminogen activator (uPA), which then binds to the membrane's uPAR (urokinase-type plasminogen activator receptor) . From the uPAR, the suPAR is created via cleavage. SuPAR has the potential to cause or modulate a variety of diseases in patients with cancer, infectious and inflammatory diseases (including HIV infections, tuberculosis, liver fibrosis, and inflammatory bowel disease). During cellular invasion, suPAR can convert plasminogen to plasmin, which degrades fibrin, activates matrix metalloproteases, and mediates proteolysis of extracellular matrix proteins. The activities of integrins, such as activating intracellular signalling, monocyte chemotaxis, cell adhesion, and proliferation, are modulated by suPAR. SuPAR level is a significant marker in patients with various diseases and has been linked to a worse outcome in a variety of infectious and non-infectious disorders, according to several studies. Lung disease biomarkers are necessary to aid in diagnosis, characterise clinical phenotypes, and track the effectiveness of both current and novel therapy approaches. In this review, we examine the potential of suPAR as an universal marker for lung disease diagnosis, prognosis, and therapeutic monitoring.